Nonfatal Suicidal Behaviors in U.S. Army Administrative Records, 2004–2009: Results from the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS) - Robert J. Ursano; Ronald C. Kessler; Steven G. Heeringa; Kenneth L. Cox; James A. Naifeh; Carol S. Fullerton; Nancy A. Sampson; Tzu‐Cheg Kao; Pablo A. Aliaga; Patti Vegella; Holly Herberman Mash; Christina E. Buckley; et al. (2015)
Objective: Although the U.S. Army suicide rate is known to have risen sharply over the past decade, information about medically documented, nonfatal suicidal behaviors is far more limited. Here we examine trends and sociodemographic correlates of suicide attempts, suspicious injuries, and suicide ideation among regular Army soldiers. Methods: Data come from the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS) Historical Administrative Data Study (HADS), which integrates administrative records for all soldiers on active duty during the years 2004 through 2009 (n = 1.66 million). Results: We identified 21,740 unique regular Army soldiers with a nonfatal suicidal event documented at some point during the HADS study period. There were substantial increases in the annual incidence rates of suicide attempts (179–400/100,000 person-years) and suicide ideation (557–830/100,000 person-years), but not suspicious injuries. Using hierarchical classification rules to identify the first instance of each soldier's most severe behavior, we found increased risk of all outcomes among those who were female, non-Hispanic White, never married, lower-ranking enlisted, less educated, and of younger age when entering Army service. These sociodemographic associations significantly differed across outcomes, despite some patterns that appear similar. Conclusion: Results provide a broad overview of nonfatal suicidal trends in the U.S. Army during 2004 through 2009 and demonstrate that integration of multiple administrative data systems enriches analysis of the predictors of such events.